PHARMACOLOGICAL SCREENING OF LEAF EXTRACTS OF ETHNOMEDICINAL PLANT, VITEX ALTISSIMA (VERBENACEAE) FOR ITS TRADITIONAL CLAIMS - JEFFREY BOSE N, MARIA FRANCIS; NATARAJAN P; MEHALINGAM P (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Vitex altissima (Verbenaceae) has been extensively used in folk medicine for the treatment of pain and associated ailments. Hence, the present study was intended to evaluate total methanolic and aqueous leaf extracts of Vitex altissima for analgesic, anti-inflammatory and antipyretic activities. Methods: The analgesic activity was studied by tail immersion model, while the anti-inflammatory activity by carrageenan induced paw oedema model and the antipyretic activity was studied by brewer's yeast-induced pyrexia model. Acute toxicity study and preliminary phytochemical screening were also studied to evaluate the toxicity and chemical profile of the both extracts respectively. Results: No toxicity profile was observed in rats after oral administration of the both extracts at the dose of 5g/kg body weight.Â  The different extracts at a dose of 200 mg/kg and 400 mg/kg body weight p.o produced a significant (p<0.05) dosage dependent inhibition of pain and oedema in analgesic and anti-inflammatory models respectively. Both extract also showed significant and dosage dependent inhibition of temperature elevation compared with the standard drug paracetamol (150 mg/kg/ body weight). Phytochemical screening of the plant extract revealed the presence of tannins, alkaloids, flavonoids and saponins, coumarins and terpenoids. Conclusion: These results indicate that leaf extracts of Vitex altissima possesses potent analgesic, anti-inflammatory and antipyretic effects and thus pharmacologically justifying its folkloric use in the management of pain and related ailments.